Numerical simulation of circulation control turbine cascade with Coanda jet and counter-flow blowing at high Mach numbers. (19th June 2017) - Feng, Y.; Song, Y.; Chen, F.
ABSTRACT: The performance of a circulation-control inlet guide vane that makes use of the Coanda effect was studied numerically in a high Mach number turbine cascade. The effect of different shapes (elliptic and circular) of the Coanda surface at the blade trailing edge was investigated by implementing both a Coanda jet and a counter-flow blowing. Under high subsonic flow conditions, with a total blowing ratio of 3% of the mainstream, the circulation control cascade can reach the same performance as the reference stator with a 13.5% reduction in the axial chord length, with minimal increase of the energy loss coefficient. The Coanda surfaces with small curvature are more efficient in entraining the mainstream flow, and they achieve better aerodynamic performance. The wall attachment of the Coanda jet is improved by employing counter-flow blowing, resulting in a slight increase of both the exit flow angle and the expansion ratio. Under supersonic flow conditions at the cascade exit, it is more difficult for the circulation control cascade to reach the appropriate flow turning due to a premature shock wave, which is absent in the original cascade until the very end of the suction surface.